NATIONAL VALUES ARE THE MAIN FACTOR THAT INCLUDES NATIONAL AND CIVIL RESPONSIBILITY FOR TODAY'S YOUTH - Suvonqulov Xusan Toirovich; Turatov Shuxrat Baxromovich (Journals Park Publishing, 2022)
The article analyzes the role of national values in the assimilation and formation of national and civic responsibility in young people today, as well as focuses on the factors affecting young people.
Keywords: national values; national responsibility; civil society